2016
DOI: 10.1111/ecc.12446
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated antigens and their anti-cancer applications

Abstract: So far, a number of tumour-associated antigens (TAAs), such as heat shock proteins, alpha-fetoprotein, carcino-embryonic antigen and others have been identified in a variety of malignant tumours. Differences in the expression levels of TAAs in cancers compared with normal cells have led to these antigens being investigated as diagnostic and prognostic biomarkers or exciting targets in cancer treatment. Here, we systematically list the current representative TAAs to shed some light on current approaches and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 71 publications
1
38
0
1
Order By: Relevance
“…The activities of AST and ALT will increase with the incidence of hepatic diseases and abnormal metabolic function. AST is an enzyme found in the liver, heart, skeletal muscles, kidneys and, to a lesser extent, in the pancreas [24]. An increase of these markers is usually associated with cardiac arrest or liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of AST and ALT will increase with the incidence of hepatic diseases and abnormal metabolic function. AST is an enzyme found in the liver, heart, skeletal muscles, kidneys and, to a lesser extent, in the pancreas [24]. An increase of these markers is usually associated with cardiac arrest or liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Yanai et al [ 5 ] reported a case of simple hepatic cyst with elevated CA19-9, while cases of hepatic cysts with elevated PIVKA-II or CA12-5 have not previously been reported. We speculate that the mechanisms for the elevation of these tumor markers may be as follows: (1) A giant hepatic cyst compresses the liver, causing injury to the hepatocytes, which may lead to secretion of a large amount of PIVKA-II; (2) Some tumor-associated antigens, such as carcinoembryonic antigen (CEA), CA19-9, CA12-5, and CA15-3, are expressed on inflammatory cells[ 12 , 13 ]. We found inflammatory cells in the patient’s cystic fluid, so we conjecture that elevated serum CA19-9 and CA12-5 levels are non-specific and might be due to the effect of inflammation; and (3) Although the exfoliative cytology examination of the patient’s cystic fluid did not have a positive finding, CT scan showed no typical characteristics of serous tumor, and the tumor marker levels were significantly decreased after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adjuvants, cytokines, and nucleic acids, there are other types of therapeutic drugs that could achieve the immunomodulatory effect for cancer treatment. Generally, cancer cells express a higher amount of tumor-associated antigens than normal cells, and some of these antigens are exclusively identified on tumor cells: tumor-specific antigens or neo-antigens [ 192 , 193 ]. But these antigens on tumor cells are usually not directly recognized by the immune system due to immune evasion of tumor cells [ 194 ], thus delivery of exogenous tumor-associated antigens into cancer cells is a feasible approach for anti-tumor immune stimulation.…”
Section: Chitosan-based Nanomedicinesmentioning
confidence: 99%